Financial and Operational Training for Culinary Businesses at the GKI Pamulang - Diana Frederica; Subagyo Subagyo; Septian Bayu Kristanto; Bambang Siswanto; Adrie Frans Assa; Tri Adi Saputra; Victor Lamberto Iskandar; Petrus Noferiman Zai (International Journal Of Community Service, 2024)
Starting a business is challenging, particularly when it comes to sustaining it. Some members of the GKI Pamulang congregation already run businesses but need growth due to stagnant or declining income. Additionally, there are congregation members who are employees interested in launching a culinary business and need guidance on getting started. The goals of this community service initiative are: (1) to provide an overview of the culinary business, (2) to inspire GKI Pamulang members to either start a culinary venture or sustain their existing businesses, and (3) to offer training on financial management (including basic financial reports, cost calculation, and taxation) and operations for culinary businesses. The activity employs lectures, case studies, presentations, and mentoring as methods. Held on May 25, 2024, at GKI Pamulang, the event was attended by 29 congregation members. Participants expressed satisfaction with the relevant material presented and gained valuable insights and motivation for starting and maintaining a culinary business, as well as knowledge on financial management and business operations.